Position of Tax Debt and Labour Right: Legal Review - Sonya Liani Ramadayanti (Borong Newinera Publisher, 2020)
This study aims to explain the position of tax debt and labour right in bankruptcy. The legal research method used in this research using normative research, the legal rules and legal principles used related to bankruptcy law, tax law and labour law will be a reference in describing the problem of the position of tax debt and labour right in bankruptcy cases. The Taxation Law gives a special treatment and higher position on which the tax debt is first to be paid by the debtor and followed by the right borne by the separatist creditor. On the other hand, Law Number 13 of 2003 concerning Employment also regulates that the labour of the wages and other rights of the labour and positioned the labour as preferred creditor on which the privilege is given by the law. However, there are no statements in the Employment Law that stated the position of labour as a preferred creditor is higher than separatist creditor in the matter of bankrupt as what the Taxation Kaw expressed creditor is higher than the separatist creditor within the matter of tax payment. That distinction seems positioned the preferred creditor status of labour is lower than the position of separatist creditor on the matter of right fulfillment in bankruptcy. It is certainty that the statement which stated that the collection of tax debts have the right to preceded than other debts does not fit in this matter. Eventually, there is a decision of Constitutional Court Number 67/PUU-XI/2013 that provides a change within the position labour’s right on the matter of bankruptcy.